Patterns and Determinants of Cross-border Financial Asset Holdings in East Asia - Jong-Wha Lee (Asian Development Bank (ADB), 2008)
This paper analyzes the patterns and determinants of financial integration in East Asia by using the data set of cross-border holdings of financial assets such as equity portfolio, long-term and short-term debt securities, and bank claims. Empirical analysis based on the gravity model of bilateral international asset holdings shows that financial integration among East Asian economies, particularly in equity and debt securities, is relatively lower than in Europe. A large part of regional financial integration in East Asia is due to heavy intra-regional trade in goods-after controlling for bilateral trade volume, East Asia's relatively lower regional integration becomes apparent. The relative lack of financial integration is due largely to underdeveloped financial infrastructure, a low level of capital account liberalization, and higher exchange volatility.
hdl:11540/1764
Keywords: F21; F36; F41; G15; 330; Cross-border portfolio investment; financial integration; East Asia; gravity model